Research of vertical migration of radionuclides in the soil at testing "Red forest" area - M. V. Zheltonozhskaya; N. V. Kulich; A. I. Lypska; L. V. Sadovnikov (Ядерна фізика та енергетика)
Researches of vertical migration of Chernobyl origin radionuclides at testing «Red forest» area in 5-km ChNPP-zone were carried out. The γ- and β- spectrometer measurements of soil samples were carried out using the anticompton spectrometer and a beta spectrometer. Presence of 60Co, 134,137Cs, 154,155Eu, 241Am to depth of 30 cm in all soil cuts was fixed. The sites with sod-low-podzol sandy soils on alluvial sands contain 137Cs, 90Sr and 241Am to depth of 60 cm. The presence 243Am and 243Cm was found in the top layers of soils at territory of testing area.